Strengthening capacities and broadening options for shelter provision a resource kit for local government (Philippines-Canada Local Government Support Program (LGSP), 2003)
The Resource kit is a handy and comprehensive reference for local governments that aim to carry out their mandate and vision for delivering shelter services.